1988
DOI: 10.1007/bf02371218
|View full text |Cite
|
Sign up to set email alerts
|

Element content in tissues of spruce seedlings from hydroponic cultures simulating acidification and deacidification

Abstract: In order to determine the primary causes of coniferous fine root damage and disfunction in acidic soils, hydroponic cultures of young spruce in pH neutral, acidic, and metal ion-amended media were established. After five months, physiological stress in the roots was removed by raising the pH in the acid and metal ion-amended cultures to physiological neutrality. The cellular element analytical techniques of x-ray microprobe (EDXA) and laser-micromass-spectroscopy (LAMMA) were applied to samples of various tiss… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0
1

Year Published

1989
1989
2008
2008

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 51 publications
(15 citation statements)
references
References 27 publications
(25 reference statements)
1
13
0
1
Order By: Relevance
“…The Mg/Al and Mg/Mn ratios of forest soil solutions in industrial areas were generally lower than non-industrial sites (data not shown). Stienen and Bauch (1988) showed that Mg uptake was reduced more than the Ca uptake in the presence of Mn in soil solution. Davis (1990) investigated soil solutions under Norway spruce (Picea abies) and found forest decline was mainly due to increased levels of Al and deficiencies of Mg.…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…The Mg/Al and Mg/Mn ratios of forest soil solutions in industrial areas were generally lower than non-industrial sites (data not shown). Stienen and Bauch (1988) showed that Mg uptake was reduced more than the Ca uptake in the presence of Mn in soil solution. Davis (1990) investigated soil solutions under Norway spruce (Picea abies) and found forest decline was mainly due to increased levels of Al and deficiencies of Mg.…”
Section: Resultsmentioning
confidence: 97%
“…In general, forest declines are often characterized by low concentrations of base cations, especially Ca (Kolb and McCormick 1993;Long et al 1997;Lee et al 2004a, b). Stienen and Bauch (1988) showed that Ca concentrations in soils limited the growth of sugar maple in north-central Pennsylvania and southern New York. Those studies showed that high Al concentrations in soils inhibited Ca uptake by trees.…”
Section: Resultsmentioning
confidence: 99%
“…Truman et al (1986) specified critical foliar levels of 800 mg kg À1 for P. radiata. For more sensitive species such as Picea abies, values of 32 mg kg À1 of Al have been proposed by Steinen and Bauch (1988) using hydroponic cultures. In this study, foliar Al levels higher than 800 mg kg À1 were generally found in all species growing on granodiorite soils, indicating the possible existence of Al stress.…”
Section: Foliar Indicesmentioning
confidence: 99%
“…Adverse effects of low pH and AI were shown for trees, particularly those grown in hydroponic cultures (e.g. Evers, 1983;Hecht-Buchholz et al, 1987;Junga, 1984;Rost-Siebert, 1983Schaedie et al, 1989;Stienen and Bauch, 1988;Tischner et al, 1983). In many acid soils throughout the world aluminium is the most important growth impeding factor (Rengel, 1992).…”
Section: Introductionmentioning
confidence: 99%